Malignant melanotic Xp11 neoplasms exhibit a clinicopathologic spectrum and gene expression profiling akin to alveolar soft part sarcoma: a proposal for reclassification. Issue 4 (2nd July 2020) - Wang, Xiao‐tong; Fang, Ru; Zhang, Ru‐song; Ye, Sheng‐bing; Li, Rui; Wang, Xuan; Pan, Rui; Liu, Chong; Chen, Jie‐yu; Zhao, Ming; Teng, Xiao‐dong; Yu, Wen‐juan; et al.
Abstract: The classification of the distinct group of mesenchymal neoplasms, first described as 'Xp11 translocation perivascular epithelioid cell tumor (PEComa)' and for which the term 'melanotic Xp11 neoplasm' or 'Xp11 neoplasm with melanocytic differentiation' has recently been proposed, remains challenging and controversial. We collected 27 melanotic Xp11 neoplasms, the largest series to date, for a comprehensive evaluation. Fourteen of the cases, together with eight alveolar soft part sarcomas (ASPS), nine conventional PEComas and a control group of seven normal tissues were submitted to RNA sequencing. Follow‐up available in 22 patients showed 5‐year overall survival and 5‐year disease‐free survival of 47.6 and 35.7%, respectively, which were similar to ASPS and significantly worse than conventional PEComa. Univariate analysis of location (occurring in the kidney versus not kidney), infiltrative growth pattern, nuclear pleomorphism, mitotic activity ≥2/50 high‐power fields (HPF), necrosis and lymphovascular invasion were found to be associated with overall survival and/or disease‐free survival. Multivariate analysis identified that location was the only factor found to independently correlate with disease‐free survival. More importantly, RNA sequencing‐based clustering analysis segregated melanotic Xp11 neoplasm and ASPS from other tumors, including conventional PEComa and Xp11 translocation renal cell carcinoma, and formed a compact cluster representative of the largely similar expression signature. Here we clearly define the true biologic nature of melanotic Xp11 neoplasms which are distinctive malignant mesenchymal tumors, rather than simply PEComa variants with occasionally unpredictable behavior. Meanwhile, melanotic Xp11 neoplasm and ASPS more likely represent phenotypic variants of the same entity, which is distinct from conventional PEComa and Xp11 translocation renal cell carcinoma. Based on these important findings, melanotic Xp11 neoplasm might be reclassified into a distinctive entity together with ASPS, independent from PEComa, in future revisions of the current WHO categories of tumors of soft tissue and bone for the improved reclassification. © 2020 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.